2007
DOI: 10.1111/j.1365-313x.2007.03295.x
|View full text |Cite
|
Sign up to set email alerts
|

HYPERSENSITIVE TO RED AND BLUE 1 and its C‐terminal regulatory function control FLOWERING LOCUS T expression

Abstract: The red and far-red light-absorbing phytochromes and UV-A/blue light-absorbing cryptochromes regulate seedling de-etiolation and flowering responses. The signaling steps that mediate the photoreceptor regulation on key flowering genes remain largely unknown. We report that a previously identified photomorphogenic mutant, hypersensitive to red and blue 1 (hrb1), flowered late and showed attenuated expression of FLOWERING LOCUS T (FT) over both long days and short days. Transgenic plants that overexpress the ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…As a proof of concept, this transient transformation system was used to analyze the subcellular localization of an Arabidopsis protein, HYPERSENSITIVE TO RED AND BLUE 1 (HRB1) (Kang et al. , 2005, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…As a proof of concept, this transient transformation system was used to analyze the subcellular localization of an Arabidopsis protein, HYPERSENSITIVE TO RED AND BLUE 1 (HRB1) (Kang et al. , 2005, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The hypersensitive to red and blue 1 ( hrb1 ) mutant has a short hypocotyl phenotype under red or blue light and a late flowering phenotype [20][21]. HRB1 is a small nuclear protein of 23 kDa with an unknown biochemical function [20], but its N-terminal ZZ-type zinc finger motif is likely involved in protein-protein interaction [22].…”
Section: Introductionmentioning
confidence: 99%
“…2006). Although AtDi19‐7/HRB1 appears to regulate phytochrome B mediated red and cryptochrome mediated blue light responses (Kang, Chong & Ni 2005; Kang et al. 2007), the function of the other gene family members has yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the seven Di19 genes present in A. thaliana are transcriptionally induced by abiotic stress, but not by ABA (Milla et al 2006). Although AtDi19-7/HRB1 appears to regulate phytochrome B mediated red and cryptochrome mediated blue light responses (Kang, Chong & Ni 2005;Kang et al 2007), the function of the other gene family members has yet to be identified.…”
Section: Introductionmentioning
confidence: 99%